Optimizing Reinforcement Requirements for Inspection Road Works Using Cutting Optimization Pro Software on the SANUR Port Project - Astariani, Ni Kadek; Partama, I Gusti Ngurah Eka; Kamasan, Anak Agung Ngurah Mayun Pradnya Putra (Universitas Ibn Khaldun Bogor, 2025)
Construction project is a long process, where in its implementation there are many problems that must be resolved. One of the problems that is often encountered is uncontrolled use of materials, resulting in construction waste. This condition occurs because the control system implemented still uses a conventional system, namely relying only on the performance of craftsmen in the field without any control over the possible patterns of cutting the remaining reinforcing waste with the type of rebar that will be used next manually. So the method for reinforcing steel work that is suitable to be carried out in the field is to prepare a Bar bending schedule (BBS). BBS is a calculation method to determine the length of each iron required, the amount of reinforcing iron to be used and the total weight of all the iron to be installed in a structure. As in the Sanur Port Project, specifically on the South Breakwater Inspection Road sub-work, where based on the calculation results, it was found that the waste level value produced based on the Bar bending schedule (BBS) method using the Cutting Optimize Pro application was smaller when compared to the manual waste level value. . Where optimization using the cutting optimization pro software compared to the manual method can optimize the use of rebar rods by 9.88% with a waste level value of 0.58%.